4t-8+14t=3-4t-11

Simple and best practice solution for 4t-8+14t=3-4t-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4t-8+14t=3-4t-11 equation:


Simplifying
4t + -8 + 14t = 3 + -4t + -11

Reorder the terms:
-8 + 4t + 14t = 3 + -4t + -11

Combine like terms: 4t + 14t = 18t
-8 + 18t = 3 + -4t + -11

Reorder the terms:
-8 + 18t = 3 + -11 + -4t

Combine like terms: 3 + -11 = -8
-8 + 18t = -8 + -4t

Add '8' to each side of the equation.
-8 + 8 + 18t = -8 + 8 + -4t

Combine like terms: -8 + 8 = 0
0 + 18t = -8 + 8 + -4t
18t = -8 + 8 + -4t

Combine like terms: -8 + 8 = 0
18t = 0 + -4t
18t = -4t

Solving
18t = -4t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '4t' to each side of the equation.
18t + 4t = -4t + 4t

Combine like terms: 18t + 4t = 22t
22t = -4t + 4t

Combine like terms: -4t + 4t = 0
22t = 0

Divide each side by '22'.
t = 0

Simplifying
t = 0

See similar equations:

| 3v+19=5v-17 | | 2-3(5)=-7 | | 12s+20=17s | | 19a-8=15a | | 4/5-(-16/5) | | -5(8a-6)=-34-8 | | 2z+20=3z-9 | | 3p+13=p+15 | | p=5.65-.05(78.4) | | 328=8(6+5a) | | 5w-14=4w+4 | | X=5y*7 | | 3(x-1)=5x+4 | | 2x-k=-1 | | X-5=2(x-20) | | 5.65-.05q=.75+.0125q | | 2-3(2)=-7 | | 10w-20=3w-36 | | 2-3(-4)=-7 | | 7+3*n=5 | | 7t+25=8+16(t+3) | | p+20=2p-17 | | 5cos^2x+2=3 | | 4/5.5/4.-3= | | 25-2b=9 | | 20c-18=14c | | -2(5s-5)-10=-2(9s+10)-3 | | 3c=2c+17 | | s-2=5-s | | Y=-0.02x^2+.5x | | 7q+2(3-2w)=4(w+2)-(w-6) | | 2(4-4)+32= |

Equations solver categories